Euro-Mediterranean relations after the Arab spring persistence in times of change - Horst, Jakob; Jünemann, Annette, 1959-; Rothe, Delf (Ashgate Publishing Ltd, 2013)
The 'Arab Spring' triggered paradigmatic shifts but, despite these changes, much in the Euro-Mediterranean region remains the same. Utilising 'Logics of Action', an innovative theoretical framework designed to capture the complexity of political interaction in one of the fastest changing regions in the world, this book discusses developments in the region before and after the Arab Spring that can be characterised by a continuation of the norm. Offering a completely new perspective on the events of the 'Arab Spring' it identifies something that seems paradoxical at first sight; persistence in t.